Neuropsychiatric Manifestation on Anti-NMDAR Encephalitis: A Case Report - Andrew W, Tanuwijaya (Acta Neurologica Indonesia, 2024)
Introduction : Anti-NMDA (N-methyl-D-aspartate) receptor encephalitis (Anti-NMDAR Encephalitis) is a rare autoimmune disorder that primarily affects the central nervous system, which is characterized by complex neuropsychiatric disorders and the presence of Immunoglobulin G (IgG) against the NR1 subunit of the NMDA-receptor in the central nervous system. This disease is one of the most commonly diagnosed autoimmune encephalitis. Frequently misdiagnosed, an accurate examination is required. Case Report : A 24-year-old female presented with continuous seizures and psychiatric disorders such as hallucinations and behavioral changes. Physical examination revealed loss of consciousness, fever, positive meningeal sign, and involuntary movement in the mouth and left hand. Immunofluorescence test revealed positive anti-NMDA antibodies, lumbar puncture revealed pleocytosis, head contrast enhanced CT-scan suggests meningoencephalitis, and electroencephalography revealed ictal and interictal epileptiform discharges. The patient is diagnosed with the Anti-NMDAR Encephalitis. Discussion : Anti-NMDAR Encephalitis is a rare autoimmune encephalitis that affects the central nervous system because the body’s immune system mistakenly attacks the NMDA receptor in the brain. The main symptoms consist of a combination of neurologic and psychiatric symptoms. Treatment of this disease could include corticosteroids, Intravenous Immunoglobulin (IVIG), and plasma exchange if necessary, followed by supportive care to treat the symptoms. Conclusion : Anti-NMDAR Encephalitis is a rare form of autoimmune encephalitis that should be included in the differential diagnosis when facing a patient with neuropsychiatric disorder, especially in patients who have never experienced psychiatric symptoms before.